ANALISIS KUALITAS MUTU PELAYANAN TERHADAP KEPUASAN PASIEN DI INSTALASI RADIOLOGI RUMAH SAKIT PURI CINERE TAHUN 2022 - Eka Pratiwi (2023)
The service quality in hospitals can affect patient satisfaction based on the services they receive. Patient satisfaction can be assessed through 5 dimensions of quality which include reliability, responsiveness, assurance, empathy, tangibles. This study aims to determine the relationship between service quality and patient satisfaction at the Radiology Installation of RS Puri Cinere in 2022 through 5 dimensions of service quality. This study used a quantitative method with a cross-sectional approach. The population in this study were all radiology patients who had received the radiology services at the Radiology Installation RS Puri Cinere. Samples were taken using a non-probability sampling technique of 100 samples and questionnaire as the research instrument. The data were analyzed using the frequency distribution and chi-square test. The results of this study indicate that there is a relationship between the dimensions of reliability (ρ=0.000), responsiveness (ρ=0.000), assurance (ρ=0.000), empathy (ρ=0.000), tangibles (ρ=0.000). This research is intended as an evaluation, assessment, and improvement in terms of service providers (radiology officers), facilities, and infrastructure to improve the quality of service at the Radiology Installation of RS Puri Cinere.